Pengaruh Promosi, Citra Merek, dan Kualitas Produk Terhadap Keputusan Pembelian: (Studi pada Konsumen Gen-Z Kopi Kenangan di Kota Tangerang) - Puji Astuti; Rina Ayu Vildayanti (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to determine the effect of Promotion, Brand Image, and Product Quality on Purchasing Decisions at Gen-Z Kenangan Coffee Consumers in Tangerang City. The sample used was 100 respondents, with Non Probability Sampling technique and Accidental Sampling method. The instrument used is a questionnaire with a Likert Scale. Data processing using IBM Statistical Package for Social Sciences (SPSS) version 26. The results showed that the Promotion variable had a significant effect on purchasing decisions, the Brand Image variable had a significant effect on purchasing decisions, and the Product Quality variable had a significant effect on purchasing decisions. In addition, the variables of Promotion, Brand Image, and Product Quality have a simultaneous effect on Gen-Z Consumers of Kopi Kenangan in Tangerang City.